The Effectiveness of Warehouse Utilization at Soekarno-Hatta Internasional Airport - Wynd Rizaldy; Suharto Abdul Majid; Charles AN (Institut Transportasi dan Logistik Trisakti, 2015)
In order to improve the performance of cargo warehouse owned by PT JAS, layout redesigning is carried out. It is to facilitate the operator in storing, moving, and carrying cargo so that these activities can run quickly and systematically with relatively low cost. By using the method of Cube per Order Index (COI) that refers to the data of import cargo movement in 2010, it is found that the utilization of PT JAS warehouse at Soekarno-Hatta international airport can still be optimized up to a hundred percent from the current condition.